Effects of integrated rice-duck farming on weed pressure, herbivore-predator interactions and economic benefits. Issue 6 (3rd June 2022) - Qian, Ping; Quais, Md Khairul; Zhou, Wenwu; Ye, Jing; Wang, Guanghua; Wu, Mengdi; Zhong, Jian; Chen, Ming; Yuan, Xin; Zhu, Jinliang; Feng, Jinxiang; Zhu, Zeng-Rong
ABSTRACT: This study was conducted to evaluate whether conventional farming can be replaced by a lower chemical pollution farming system, integrated rice-duck farming in a suburban agricultural area in northern Zhejiang, Southeast China. We comprehensively assessed the impacts of integrated rice-duck farming on weeds and herbivorous insects along with their natural enemies during the rice-growing season. We found that the rice-duck system effectively controlled weeds within the paddy fields. Nevertheless, the abundance of herbivores, particularly planthoppers and leafhoppers was increased in the duck-roaming paddy fields compared to the control and conventional fields, indicating the inefficiency of the rice-duck system in the control of rice main herbivore pests. Rice-duck farming significantly reduced the abundance of predators, especially spiders and dragonflies, therefore an 'enemy-free space' was created for herbivores which might be responsible for the observed herbivore increase in the rice-duck fields. Despite the inefficiency of rice-duck farming in the control of rice main herbivore pests, the net income of the rice-duck treatment with an organic certification was 7.6 and 1.4 times higher compared to the conventional and control treatments, respectively. In the view of the favourable results obtained in this study, the integrated rice-duck farming system might be suggested as a high economic return organic farming method suitable for modern farmers.